Análise dos registros de escolaridade na RAIS de doutores titulados em universidades brasileiras - Daniel Gama e Colombo; Priscila Koeller (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– Administrative records are essential for official statistics and the design of public policies. This article investigates the accuracy of the "level of education/schooling" information in the employment records of PhDs in the Annual Social Information Report (Rais) for the 2013-2021 period, considering the graduates of Brazilian doctoral programs within this period. The analysis is performed by merging RAIS information with the database of graduate students in Brazil. The results indicate a high level of inaccuracy in the information of education of PhD employees, with only 45% of correct records when considering those who earned a doctoral degree up to eight years before the RAIS base-year. A greater accuracy rate was found for individuals who earned their degrees longer ago or before the beginning of the employment contract. Furthermore, the proportion of incorrect records is greater for the public sector and noneducational organizations. Among the latter, public organizations at the subnational levels and private organizations that are either small or nonknowledge intensive present lower accuracy rates in the information.
Keywords: Y10; I29; J49; 330; doctorate; Rais; administrative records; employment of PhDs